2003
DOI: 10.1139/b03-049
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of seed development and maturation in beach pea (Lathyrus maritimus)

Abstract: The developmental patterns of seed, seed coat, and hardseededness were studied in naturally growing crop plants of beach pea (Lathyrus maritimus (L.) Bigel.) at six reproductive growth stages (S1-S6). Grass pea (Lathyrus sativus L.) seeds were used for comparison in some experiments. The accumulation of fresh and dry weight in pod shell and seed of beach pea and pod shell of grass pea followed an almost sigmoidal pattern. However, grass pea seed showed a linear pattern of weight accumulation. During maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…In the case of S. muricatus , seeds achieved 70% germination at 60% of the maximum dry weight accumulation (23 DAA), while complete germination was reached at 90% of maximum dry weight (34 DAA). These findings agree with those of Chinnasamy and Bal (2003) for Lathyrus spp. and with those of Revell et al (1999) for yellow serradella (Ornithopus compressus L.).…”
Section: Discussionsupporting
confidence: 92%
“…In the case of S. muricatus , seeds achieved 70% germination at 60% of the maximum dry weight accumulation (23 DAA), while complete germination was reached at 90% of maximum dry weight (34 DAA). These findings agree with those of Chinnasamy and Bal (2003) for Lathyrus spp. and with those of Revell et al (1999) for yellow serradella (Ornithopus compressus L.).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies on seed development have shown that the transition from a permeable to impermeable seed coat coincides with the decline in moisture content during the maturation drying phase of seed development (Jaganathan 2016). Indeed, it has been observed in a few species that the seed coat becomes impermeable only when the moisture content of the seeds falls to a specifi c threshold level (Hyde 1954;Gladstones 1958;Egley 1979;Chinnasamy & Bal 2003;Hay et al 2010;Gama-Arachchige et al 2011;Gresta et al 2011). Th us, the number of seeds with impermeable seed coats produced by plants may vary between sites or within years based on the moisture content reached during maturation drying, which is aff ected by the environmental conditions including temperature and relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…germination hard seededness completely prevents imbibitions (Chinnasamy and Bal, 2003). Seeds may germinate at temperature as low as 2-3° C. Plants are able to withstand frost as cold as -8°C.…”
Section: Duringmentioning
confidence: 99%
“…The accumulation of fresh and dry weight in fruit walls and seeds during development indicate that fruit walls follow a sigmoid curve, while seeds follow a linear trend. During maturation, moisture content of fruit walls and seeds decreases due to dehydration (Chinnasamy and Bal, 2003). On dry weight basis of seed, content of starch, protein, lipid and thiamine increases, while soluble sugars, sugars, total amino acids, essential and sulphur amino acids, ash and its alkalinity, magnesium, phosphorus, vitamin C, riboflavin, carotenoids, p-carotene, and chlorophyll also increased.…”
Section: Reproductive Growthmentioning
confidence: 99%
See 1 more Smart Citation